2009
DOI: 10.2118/106998-pa
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Element Studies of Near-Wellbore Region During Cementing Operations: Part I

Abstract: Summary A wellbore cement sheath is expected to provide zonal isolation and borehole integrity during well construction and well life. Mechanical interactions of the cement sheath to existing and operationally induced stresses, along with other elements in proximity to the wellbore, have increasingly large technical, economic, and environmental ramifications. Staged-finite-element procedures during well construction consider sequentially the stress states and displacements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…This is a most common assumption in rock-mechanical well models (see e.g. Gray et al (2009)), and it is valid as long as the well is sufficiently long and straight.…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
“…This is a most common assumption in rock-mechanical well models (see e.g. Gray et al (2009)), and it is valid as long as the well is sufficiently long and straight.…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
“…Consequently, more accurate mechanical strength models and better assessment of cement integrity are necessary to reduce the risk of failure. Numerical simulation is commonly applied to investigate the mechanical integrity of cement [2], also by using some software such as ABAQUS [3,4], ANSYS [5], and ADINA [1]. In all types of applications, an accurate well cement stress–strain model is required.…”
Section: Introductionmentioning
confidence: 99%
“…Removing the casing in certain areas is one method of mitigating the leakage caused by a poor bond or debonding between the casing and cement. If wells are plugged and abandoned permanently, both Gray et al (2009) and Carlsen and Abdollahi (2007) suggested removing the casing steel before placing the final cement plugs. This removes the most likely leakage pathway along the casing.…”
Section: Remedial Workover Methods To Improve Wellbore Integritymentioning
confidence: 99%
“…The advantage of building the model in several steps is the ability to observe and record stress and deformation changes after each loading. Furthermore, knowing previous deformation and loading history will help to specify the initial stress state before final thermal and mechanical loads are applied to the model (Gray et al 2009). …”
Section: Near-wellbore Leakage Pathways and Simulationsmentioning
confidence: 99%